2020
DOI: 10.1182/blood-2020-134362
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival and Gradual Recovery of B Cells in Patients with Refractory Large B Cell Lymphoma Treated with Axicabtagene Ciloleucel (Axi-Cel)

Abstract: Background: Axi-cel is an autologous anti-CD19 chimeric antigen receptor (CAR) T cell therapy approved for the treatment of patients (pts) with relapsed/refractory large B cell lymphoma (LBCL) with ≥ 2 prior systemic therapies. ZUMA-1 is the multicenter, single-arm, registrational Phase 1/2 study of axi-cel in pts with refractory LBCL. In a 2-year analysis of ZUMA-1 (median follow-up, 27.1 months; N=101), axi-cel demonstrated objective response, complete response (CR), and ongoing response rates of 83%, 58%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 0 publications
2
35
0
Order By: Relevance
“…The authors concluded that MCMs better predicted Kaplan-Meier data available from the updated ZUMA-1 trial published in 2018 [55]. Following the presentation of this validation exercise, more recent ZUMA-1 trial data, with median follow-up of 39.1 months and with a median OS of 25.8 months, were presented at ASH 2020 [66]. Continuing to re-evaluate the appropriateness of survival extrapolation techniques using the most recent clinical trial extension data will serve to strengthen survival analyses and its outputs.…”
Section: Opportunities For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that MCMs better predicted Kaplan-Meier data available from the updated ZUMA-1 trial published in 2018 [55]. Following the presentation of this validation exercise, more recent ZUMA-1 trial data, with median follow-up of 39.1 months and with a median OS of 25.8 months, were presented at ASH 2020 [66]. Continuing to re-evaluate the appropriateness of survival extrapolation techniques using the most recent clinical trial extension data will serve to strengthen survival analyses and its outputs.…”
Section: Opportunities For Future Researchmentioning
confidence: 99%
“…Continuing to re-evaluate the appropriateness of survival extrapolation techniques using the most recent clinical trial extension data will serve to strengthen survival analyses and its outputs. As a result, follow-on analyses to our qualitative assessment could compare extrapolated survival data from early clinical trial reports for axi-cel and tis-cel to observed survival from longer follow-up clinical trial reports [66,67]. In addition to extended clinical trial data, real-world observational data could also be used to confirm extrapolation techniques.…”
Section: Opportunities For Future Researchmentioning
confidence: 99%
“…Interestingly, about 90% of patients had polyclonal B-cell recovery (including memory B-cells) and 60% of responding patients still had CAR+ T cells detected in blood, similar to the NCI experience. 58…”
Section: Clinical Experience With Axi-celmentioning
confidence: 99%
“…The latest long-term follow-up from the ZUMA-1 study (median follow-up 39.1 months) was presented at the ASH annual meeting in 2020 and reported durable responses with 47% 3 years overall survival. 20 Tisagenlecleucel is a second-generation anti-CD19 CAR-T construct that is commercially available for use in patients with relapsed/refractory DLBCL following at least two lines of prior therapy. In the phase 2 JULIET study, 93 relapsed/refractory DLBCL patients received tisagenlecleucel infusion.…”
Section: Car-t Cells In Clinical Trials For Lymphomamentioning
confidence: 99%